The Influence of Ismail Al-Faruqi to Islam in America - Quds, Haris Sibghatullah Fil; Fuad, Muhammad (UI Scholars Hub, 2022)
The spreading of Islam is one of the dynamic aspects of America. Islam has been brought to America by various people from different ethnicities, nationalities, and community backgrounds. This makes Islam in America appears in so many faces. One of the big moments of the history of Islam in America is the immigrant wave from Middle East which created new domination amongst American Muslims. This paper discusses one of the prominent figures from that era whose influences are big enough at that time and can still be seen today in America: Ismail Raji al-Faruqi. The researcher used a library study in writing this paper by using writings of al-Faruqi as primary data sources and other researchers’ writings as secondary data sources. This research concluded that there was some sort of dynamics of influence between al-Faruqi and America. It means that on one hand, al-Faruqi influenced Islam in America, but on the other hand, American social-cultural conditions also influenced al-Faruqi at some level.